Effect of Ferrous Gluconate on Chromosomal Abnormality Index of Allium Cepa Root Tip - Nergis Kaya (Turkish Journal of Agriculture: Food Science and Technology)
In completed research, ferrous gluconate -a food additive- used to preserve black color to prevent discoloration during storage in ripe black olives, and Allium cepa L. species. A. cepa L. roots were treated with different doses of ferrous gluconate. The effective concentration EC50 (0.068 g/l) was determined. A. cepa root tips were treated with EC50/2 (0.034 g/l), EC50 (0.068 g/l), 2XEC50 (0.136 g/l) dose for 24, 48, 72 hours, and afterward, the root tips were prepared for observation under the light microscope according to the method of preparing mitotic preparation. Chromosomal abnormality index (CAI) and genotoxic effect of ferrous gluconate in A. cepa root tip cells were determined. Repeated measurement ANOVA and TUKEY multiple comparison tests were used to investigate the effect of time and dose together on genotoxicity. C-mitosis, polyploidy, polar shifting in anaphase, polar shifting in telophase, equatorial plate shifting, laggard chromosome was observed by microscope. The highest CAI (70.16±4.85) was observed at 72h for 2XEC50 dose. Chromosomal aberration is also observed in control group. While the most common chromosomal aberration is determined as C-mitosis; The least observed chromosomal aberration is determined as polyploidy. Research results revealed that ferrous gluconate has a genotoxic effect on the root tip of A. cepa.